Isolation and identification of lactid acid bacteria originated from king grass (Pennisetum purpureophoides) as candidate of probiotic for livestock - Santoso B; Maunatin A; Hariadi BT; Abubakar H (Jurnal Ilmu Ternak dan Veteriner, 2013)
A study was conducted to isolate and identify strain of lactic acid bacteria (LAB) isolated from king grass, and to determine their potential as candidate of probiotic for livestock. The LAB was isolated by culturing king grass extract in De Man, Rogosa and Sharpe (MRS) medium. The pure culture LAB was used to identify strain of bacteria using Analytical Profile Index (API) 50 CH kit. The result showed that the strain bacteria was identified as Lactobacillus plantarum. L. plantarum was able to survive in extreme condition at pH 2 and 0.3% bile salt. L. plantarum also survived against pathogenic bacteria i.e. Staphylococcus aureus, Escherechia coli and Salmonella thypi. It is concluded that L. plantarum isolated from king grass could potentially to be used as probiotic for livestock. Key Words: Bile salt, Lactic acid bacteria, Pathogen, Probiotic, pH.